(untitled) (Research, Society and Development, 2022)
The present study aims to analyze the eating attitudes of university professors in the health area. A cross-sectional quantitative study was carried out in a private higher education institution in the city of Fortaleza-CE from September to December 2018. The sample consisted of 226 university professors from courses in the health area. A self-administered questionnaire was applied to obtain socioeconomic data, such as gender, age, course, marital status, weekly workload, place and time of meal, as well as the Eating Attitudes Test (EAT-26) in its version validated in Brazil. According to the results, 143 (63.2%) teachers from the total sample were available to answer the questionnaires, of which 96 were female (67.1%) and 47 were male (32.9%). With regard to the test of eating attitudes performed, it was found that 104 teachers (73%) are not at risk of developing a possible ED, unlike the other 39 (27%). It is concluded that through the results obtained, the absence of risk for the development of eating disorders was observed in most of the interviewees. In this context, the results may contribute to future studies in relation to teachers’ eating habits and their possible influence among students.